Unexpected Remission of Bilateral Hyperaldosteronism After Unilateral Cortisol-Producing Adenoma Resection: A Report of Two Cases - Kazunari Hara; Masanori Murakami; Kumiko Shiba; Kazutaka Tsujimoto; Chikara Komiya; Kenji Ikeda; Kurara Yamamoto; Towako Taguchi; Takumi Akashi; Soichiro Yoshida; Kenichi Ohashi; Yasuhisa Fujii; et al. (Case Reports in Endocrinology)
Primary aldosteronism (PA) is the most frequent cause of secondary hypertension. PA is primarily categorized into two subtypes: The unilateral subtype, which mainly consists of aldosterone-producing adenoma (APA) and the bilateral subtype, in which aldosterone is overproduced by both adrenal glands. Rarely, does the bilateral form of PA coexists with a cortisol-producing adenoma (CPA), as documented by previous reports. In this context, we present two cases wherein the preoperative diagnosis identified the bilateral form of PA accompanied by a unilateral CPA. However, postresection of the CPA, unexpected resolution of the bilateral form of PA was observed in both patients. Case 1：A 57-year-old female presented with overt Cushing’s syndrome attributed to a left adrenal tumor and concomitant bilateral PA. Laparoscopic left adrenalectomy was performed for the treatment of Cushing’s syndrome. Case 2：A 67-year-old female diagnosed with a left adrenal tumor with coexisting bilateral PA. The left adrenal tumor exhibited mild autonomous cortisol secretion (MACS) and given the increase in tumor size, laparoscopic left adrenalectomy was undertaken. After 1 year of surgery, we conducted a captopril challenge test (CCT) on both patients, revealing that neither satisfied the diagnostic criteria for PA. In patients where unilateral CPA coexisted with bilateral PA, unilateral adrenalectomy may provide remission of not only the autonomous cortisol secretion but also bilateral PA. Consequently, postoperative evaluation of PA assumes significance.